1985
DOI: 10.1111/j.1469-7610.1985.tb00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Firesetters: A Clinical Investigation

Abstract: The demographic, symptomatic, psychosocial and diagnostic profile of 104 child firesetters was investigated in a controlled case note and item sheet study of all children referred to an Inner London clinic between 1973 and 1981. Firesetters form a subgroup of severe conduct disorders, and are distinguished by a younger peak age of 8, higher boy/girl ratio and more marked psychosocial disturbance. The paper focuses on the relationships between background factors and firesetting, and also examines the relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Previous researchers (e.g., Forehand et al 1991;Jacobson 1985;Kolko et al 1985;Patterson 1982;Stickle and Blechman 2002) have argued that juvenile firesetters and other antisocial youths fall along the same continuum of disordered conduct, but with firesetters typically being at the upper extreme of this behavioral continuum. The present findings are consistent with this conceptualization, and extend it to include one specific aspect of cognitive functioning.…”
Section: Discussionmentioning
confidence: 98%
“…Previous researchers (e.g., Forehand et al 1991;Jacobson 1985;Kolko et al 1985;Patterson 1982;Stickle and Blechman 2002) have argued that juvenile firesetters and other antisocial youths fall along the same continuum of disordered conduct, but with firesetters typically being at the upper extreme of this behavioral continuum. The present findings are consistent with this conceptualization, and extend it to include one specific aspect of cognitive functioning.…”
Section: Discussionmentioning
confidence: 98%
“…There are very few community sample studies of firesetting, which is understandable since it is illegal and thus likely to be kept secret. The majority of epidemiological studies have focused on pyromania in childhood and adolescence and have reported the prevalence to be between 2.4% [40] and 3.5% [41, 42] (Table 1). In addition, several lines of evidence indicate that adolescent boys may be at higher risk for firesetting than adolescent girls [43, 44].…”
Section: Icds’ Phenomenology Epidemiology and Relationship With Ocdmentioning
confidence: 99%
“…Furthermore, the child was very young for a fire-setter. In a clinical investigation of 104 child fire-setters, Jacobsen (1985) found that less than 3% of children in their sample were younger than 5 years old. The presence of these atypical features provide indirect support for a relationship between the behavior change and the thyrotoxieosis factitia.…”
Section: Case Discussionmentioning
confidence: 98%